Nursing regimens: Effects on body condition, return to postpartum ovarian cyclicity in Santa Ines ewes, and performance of lambs - Ascari, I. J.; Alves, A.; Pérez, J. R O; Lima, R. R.; Garcia, I. F F; Nogueira, G. P. [UNESP]; Junqueira, F. B.; Castro, T. R.; Aziani, W. L B; Alves, N. G. (Elsevier, 2013)
The effects of nursing regimens on the body condition, onset of ovarian cyclicity postpartum and weaning weight of lambs were assessed in Santa Ines ewes. Thirty-two ewes were blocked according to parity, number of lambs, and body weight at lambing and within each block randomly allocated to treatments: continuous nursing (CN), controlled nursing (CN2) with two daily feedings for an hour after the 10th day postpartum, or early weaning (EW) with total separation from the lambs after the 10th day. The animals were evaluated from the 12th day postpartum until the first estrus or until 60th day. The dry matter and nutrients intake did not differ among treatments ( P>. 0.05) but did differ over time ( P<. 0.01). The weight, body condition score, serum concentrations of non-esterified fatty acids and prolactin, the percentages of ewes in estrus, of ewes that ovulated within 60th day and had ovulation silent, the period from lambing to estrus, ovulation and follicle with a diameter ≥5. mm and the maximum follicular diameter did not differ ( P>. 0.05) among the treatments. The percentage of ovulation until 30th day was greater ( P<. 0.05) in the EW group. The percentage of short luteal phases was higher in the CN2 and EW groups ( P=0.07) and normal luteal phases were higher in the CN group ( P=0.01). Lamb weight weaning was lower in the EW group ( P<. 0.05). It is possible to use CN to obtain lambing periods less than eight months in Santa Ines ewes, with the advantages of simpler management and higher lamb weaning weights. © 2013 Elsevier B.V.
Keywords: Follicular development; Non-esterified fatty acids; Progesterone; Prolactin; Short luteal phases; Weaning weight of lambs; Animalia; Ovis aries